Antimicrobial and antioxidant activities of \(Antheroporum harmandii\) Gagnep. collected from Quang Tri province - Chi Mai, Nguyen; Khac Ban, Ninh; Huong Giang, Vu; Xuan Diep, Hoang; Thi Hoe, Pham; Tuong Van, Nguyen; My Linh, Tran (Academia Journal of Biology, 2023)
Antheroporum harmandii Gagnep. is a native plant species of Vietnam, belonging to a small genus of the Fabaceae family. In this study, the bioactivities of different extracts from twigs and seeds of A. harmandii plants collected from Dakrong, Quang Tri province were evaluated. Antimicrobial and antioxidant activities of plant extracts had been done using an agar well diffusion method and DPPH assay. The results showed that methanol, dichloromethane and ethyl acetate extracts from twigs and methanol extract from seeds exerted activities to significantly inhibit two out of nine tested microorganisms. Particularly, the dichloromethane extract from the twigs sample exhibited the highest activity to Micrococcus luteus and Staphylococcus aureus strains with inhibition zones of 4.7 ± 0.3 mm and 2.3 ± 0.2 mm, respectively, at concentrations of 50 mg/mL. The lowest MIC values (500 µg/mL) and 50% inhibition concentration values (IC50) against M. luteus and S. aureus were recorded for the methanol and dichloromethane extracts of twigs. Among tested extracts, the ethyl acetate extract of twigs was the strongest antioxidant, showing radical scavenging potential with IC50 of 117.24 μg/mL. Therefore, A. harmandii species can be suggested as a new source for the isolation of valuable natural compounds.